“Influencia del proceso de diseño y desarrollo bajo ISO 9001:2015 en los programas de capacitación continua sobre el cumplimiento de los esquemas de certificación evaluado bajo juicio experto en la empresa GICA Ingenieros” - Castillo Alva, Robert William (2019)
ABSTRACT In this research work was carried out the implementation of a design and development process (D & D) for the Quality Management System (QMS) under ISO 9001: 2015 number 8.3 of design and development applied to continuous training programs, with the objective of fulfilling the strategic objective, quality objective, scope, planning and control, audits, validation and verification of the design and development process, in the company GICA Ingenieros. The research was carried out under the philosophy of continuous improvement, process-based management, the Deming cycle (Plan-Do-Check-Act;) and compliance with the requirements of ISO 9001: 2015 number 8.3 of design and development applied to continuous training programs, for this the methodology of implementation of the design and development process of GICA Ingenieros was used. This methodology has levels aligned to Annex SL (context of the organization, leadership, planning, support, operation, performance measurement and improvement) being grouped into 05 levels called: Initial Organizational Context, Planning, Operation, Control and Final Organizational Context. The development of 05 levels is divided into 17 phases, in order to distinguish the strategy, tactics and operations, comprised of strategic management, quality management system, and the design and development process respectively. These phases are: Alignment of strategic objectives and quality objectives, Initial diagnosis and planning, Alignment of D & D process to the organizational context, Commitment from senior management, Risk management, and Objectives and planning of D & D process, Support, Implementation of D & D process, Measurement and Control of D & D, Verification and validation of D & D, Change management of D & D, Internal audits, system Measurement and Control, and Revision by the management, External audits, Final diagnosis and verification, Final Control and improvements. The 17 phases are operationalized through 52 steps generating documented data to provide compliance evidence. The design and development process, has the following subprocesses: Curricular design, ERP Synchronization with virtual classroom, Content development, Audiovisual, Load in virtual classroom, Validation and Change management. We worked with 26 academic programs divided into 2 periods, 16 academic programs for period I (May 2017 to June 2018) and 10 academic programs for period II (July 2018 to November 2018), complying with D&D planning and control. The effectiveness before the Implementation was 50%, after the Implementation in Period I it was 100% and in Period II it was 100%, complying with the scope, quality objective, planning and control, internal and external audits, verification, validation of number 8.3 from ISO 9001: 2015; the benefit is the increase of the SGC's scope from 47% to 100%, obtaining as a result the ISO 9001:2015 certification for Gica Ingenieros From the research it is concluded that the implementation of a design and development process under ISO 9001: 2015 number 8.3 in GICA Ingenieros complies with the strategic objective of providing continuous training services based on competencies aligned with certification schemes.